CIKARD - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
CIKARD (Centre for the Promotion of Indigenous Knowledge in Agriculture and Rural Development), which is based in the United States, is collecting, analyzing and disseminating information on traditional knowledge in agriculture, livestock, health,...